Peningkatan Pengetahuan Dan Pelatihan Senam Hamil Untuk Menurunkan Nyeri Punggung Pada Ibu Hamil Trimester III Di Desa Pasuruhan Kab. Pati - Siti Ni’amah; Sri Hadi Sulistiyaningsih (Jurnal Pengabdian kepada Masyarakat Cahaya Negeriku, 2021)
Background: Back pain in pregnancy is caused by progesterone and relaxin and changes in body posture and increased weight being carried into the uterus. Efforts can be made by pregnant women to reduce back pain complaints including; Relaxation, hypnosis, acupuncture, massage. (Andarmoyo, 2013). In addition, the skin stimulation technique used is the provision of cold compresses or warm compresses (Istiqomah, 2007). While the exercises that can be done by pregnant women to reduce back pain are; improve posture, do prenatal yoga, walk, swim, and do pregnancy exercises. Purpose: In order to increase the knowledge of pregnant women about pregnancy exercise to reduce back pain for pregnant women. Method: Providing transfer of knowledge to pregnant women by conducting counseling about pregnancy exercise and providing training to pregnant women about pregnancy exercise. Results: Pregnant women understand the steps of pregnancy exercise correctly and are able to practice pregnancy exercise.Conclusion: after doing community service about pregnancy exercise training, back pain complaints in pregnant women are reduced.